Evaluating the Performance of an LBS-Based Waste Reporting Application for Digital Waste Management - Umar, Najirah; Asrul, Billy Eden William; Wabula, Yuyun (Politeknik Negeri Batam, 2025)
The escalating volume of urban waste in Indonesia presents a serious challenge, exacerbated by conventional reporting mechanisms that are slow and inefficient. This study aims to develop and evaluate E-Trash, a Location-Based Services (LBS) application designed to accelerate the workflow of participatory waste reporting, handling, and monitoring in Makassar City. The novelty of this research lies in the synergistic integration of citizen reporting, real-time bidirectional notifications between reporters and field officers, and a spatial monitoring dashboard for policymakers, validated through direct, real-world implementation. The research methodology employs a software engineering approach utilizing a prototype model. System validation was conducted in three stages: black-box testing on 24 core features, performance testing under various bandwidth conditions, and a two-week field trial involving community members and sanitation personnel in two sub-districts. The findings robustly conclude that the E-Trash application effectively leverages a digital, Location-Based Services (LBS) approach to significantly enhance citizen participation in waste reporting and improve the response efficiency of sanitation personnel. The system demonstrated optimal functionality across diverse network conditions and device types, with stable response times and a high data transmission success rate affirming its reliability. Field implementation notably yielded a reduction in illegal waste accumulation and an increase in overall handling efficiency, primarily facilitated by the bidirectional notification system between citizens and sanitation teams. Consequently, E-Trash emerges as a highly viable candidate for replication in other urban settings, serving as a robust, community-participation-centric smart solution for sustainable urban sanitation management.